Dari Kompensasi ke Kinerja: Peran Mediasi Kesejahteraan dan Komitmen dalam Mewujudkan Tujuan Pembangunan Berkelanjutan (SDGs) - Muhammad Adhimawan Wijaya; Dewi Hudiyah; Rena Augia Putri; Yeni Fajrin; Citra Savitri (Universitas Nusantara PGRI Kediri, 2026)
This study aims to analyze the influence of compensation strategies on employee well-being and its implications for employee commitment and performance within the framework of achieving the Sustainable Development Goals (SDGs). Using a quantitative approach, data were collected from employees in the manufacturing sector in West Java through a structured survey. Structural Equation Modeling (SEM) was used to examine the relationships between variables. The results indicate that fairly and sustainably managed compensation positively impacts employee well-being. Furthermore, employee well-being is proven to be a key mediating factor between compensation and organizational commitment. Strong commitment then has a significant impact on improved employee performance. These findings confirm that compensation strategies aligned with sustainability principles not only support organizational goals but also directly contribute to the achievement of SDG 3 (Healthy and Well-Being Lives), SDG 8 (Decent Work and Economic Growth), and SDG 10 (Reduced Inequality). This study provides theoretical and practical implications for the development of human resource management oriented towards building a sustainable work ecosystem.